New Media for Increasing Sporulation and Germination of Phaeoisariopsis griseola Conidia - Stenglein, Sebastián Alberto (2006)
The slow growth rate of the fungus Phaeoisariopsis griseola and the availability of a homogeneous highly concentrated inoculum is an important constraint for pathogenicity or virulence studies, where plant inoculations are needed. Therefore, the purpose of this paper was to evaluate the effect of supplementing culture media with Amaranthus cruentus seed meal on fungal growth and sporulation of isolates of P. griseola belonging to the Mesoamerican and Andean groups. The amendment of PDA or V8 media with A. cruentus seed meal resulted in a considerable increase in the number of conidia and also in their capacity to germinate; this depended mostly on the stage of maturity of conidia. Mesoamerican and Andean isolates produced a different number of conidia when cultured in vitro. Furthermore, while in Mesoamerican isolates a second degree polynomial represented the relationship between number of conidia and amount of A. cruentus supplementation, in Andean isolates the relationship was linear. It seems that either one or several of the nutritional factors provided by A. cruentus contributed to the increased production of conidia and their development, resulting in faster development of the disease and an earlier appearance of symptoms. Therefore, for cultural studies, especially for inoculum production and for pathogenicity evaluations, supplementation of the media with A. cruentus seed meal proved to be a good alternative.